Вы находитесь на странице: 1из 11

DERIVATIVES

Definition: The derivative of a function f at a point a, denoted by f (a), is

f ( a h) f ( a )
f (a ) lim
h 0 h

provided that the limit exists.

If we denote y = f (x), then f (a) is called the derivative of f, with


respect to (the independent variable) x, at the point x = a.

Recall that the value of this limit is, if it exists, is the slope of the line
tangent to the curve y = f (x) at the point x = a. As well, it also represents the
instantaneous rate of change, with respect to x, of the function f at a.
Therefore, a positive f (a) means that the function f is increasing at a, while
a negative f (a) means that f is decreasing at a. If f (a) = 0, then f is neither
increasing nor decreasing at a.

Equivalently, the derivative can be stated as

f ( x) f (a )
f ( a) lim
x a xa
ex. Let f (t) = t5 + 6t , find f (a).

f ( a h) f ( a ) [(a h) 5 6(a h)] [a 5 6a ]


f (a ) lim lim
h 0 h h 0 h

[a 5 5a 4 h 10a 3 h 2 10a 2 h 3 5ah 4 h 5 6a 6h] [a 5 6a]


lim
h0 h

5a 4 h 10a 3 h 2 10a 2 h 3 5ah 4 h 5 6h


lim
h 0 h

h(5a 4 10a 3 h 10a 2 h 2 5ah 3 h 4 6)


lim
h 0 h

lim (5a 4 10a 3 h 10a 2 h 2 5ah 3 h 4 6) 5a 4 6


h 0
ex. Let f ( x) 4 x 2 5 , find f (a). Write an equation of the line tangent to
y = f (x) when a = 1.

f ( a h) f ( a ) 4(a h) 2 5 4a 2 5
f (a ) lim lim
h 0 h h 0 h

4( a h) 2 5 4a 2 5 4(a h) 2 5 4a 2 5
lim
h 0 h 4(a h) 2 5 4a 2 5

4( a h) 2 5 ( 4a 2 5) 4a 2 8ah 4h 2 5 4a 2 5
lim
h0

h 4(a h) 2 5 4a 2 5 lim
h0

h 4( a h) 2 5 4a 2 5
8ah 4h 2 8a 4h
lim
h 0

h 4( a h) 2 5 4a 2 5 lim
h 0
4( a h) 2 5 4a 2 5

8a 4(0) 8a 4a

4( a 0) 5 4 a 5
2 2
2 4a 5 2
4a 2 5

At a = 1, the point on the curve, (a, f (a)) is (1, 3), and the slope of the
4
tangent line is f (1) .
3
The equation of the line is, in point-slope form, therefore

4
y 3 ( x 1)
3

or, in slope-intercept form,

4 5
y x .
3 3
1
ex. Let f ( x) , find f (a).
x 3
2

1 1

f ( a h) f ( a ) ( a h) 3
2
a 3
2
f ( a ) lim lim
h 0 h h 0 h

1 1

( a h) 32
a 3
2
( a h) 2 3 a 2 3
lim
h 0 h ( a h) 2 3 a 2 3

a 2 3 ( a h) 2 3
lim
h 0
h( (a h) 2 3 )( a 2 3 )

a 2 3 ( a h) 2 3 a 2 3 ( a h) 2 3
lim
h 0
h( ( a h) 2 3 )( a 2 3 ) a 2 3 ( a h) 2 3

(a 2 3) ( a 2 2ah h 2 3)
lim
h0
h( ( a h) 2 3 )( a 2 3 )( a 2 3 (a h) 2 3 )

2ah h 2
lim
h0
h( ( a h) 2 3 )( a 2 3 )( a 2 3 (a h) 2 3 )

2a h 2a
lim
h 0
( (a h) 3 )( a 3 )( a 3 (a h) 3 )
2 2 2 2
( a 3 )( a 2 3 )(2 a 2 3 )
2

( a 3) 3 / 2
2
The Derivative as a Function

The derivative of a function of x is another function of x.

Up until this point, derivatives of functions were calculated at some


arbitrary, but fixed, point a. Notice from the previous examples that the
expressions obtained can be evaluated at different values of a. Indeed, we
can replace the number a in a derivative by the variable x in the expression,
and represent the derivative as a function of x.

Definition: The derivative of a function f is the function f , defined by

f ( x h) f ( x )
f ( x) lim
h0 h

for all x for which this limit exists.

The domain of f is the set of all values from the domain of f where the
above limit exists. The process of finding the derivative of f is called
differentiation of f. Geometrically, the value of f (x) represents the slope of
the line tangent to the curve y = f (x) at the point (x, f (x)).

If a is a number in the domain of f where the derivative exists, then f


is said to be differentiable at a. A function is said to be differentiable on an
open interval (a, b) if it is differentiable at every point in the interval. For
closed intervals, the limit definition of differentiability at an endpoint is
replaced by the appropriate one-sided limit.

Notations: Suppose y = f (x), then its derivative with respect to x, is


commonly denoted by

dy df d
f (x) = y = f ( x) f y D f (x) = Dx f (x)
dx dx dx
d
The symbols dx
and D are called differential operators. They are used to
explicitly denote the differentiation of the function that follows.

ex. Differentiate f (x) = x3 7x + 4

f ( x h) f ( x) [( x h) 3 7( x h) 4] [ x 3 7 x 4]
f ( x ) lim lim
h 0 h h 0 h

[( x 3 3 x 2 h 3 xh 2 h 3 ) 7 x 7 h 4] [ x 3 7 x 4]
lim
h 0 h

3 x 2 h 3 xh 2 h 3 7 h
lim lim (3 x 2 3 xh h 2 7) 3 x 2 7
h 0 h h0

How a function can fail to be differentiable

What are the types of points at which a function f is not differentiable?

1. At a corner or a cusp point

ex. f (x) = x, at x = 0

2. Where there is a vertical tangent line at a point where f is continuous


but that lim f (x) = or .
xa

ex. f ( x) 3 x , at x = 0

3. At any discontinuity (of any type) of f

ex. f (x) = x
On the interval (, 0), the curve is a line of slope 1. On the interval
(0, ), however, the curve is a line of slope 1. Therefore, letting x = 0 and
use the limit definition of derivative,

0h 0 0h 0
lim 1 , and lim 1.
h0 h h 0 h

Since the one-sided limits are not equal, the limit does not exist, so
f (x) = x is not differentiable at 0.

Theorem: If f is differentiable at a, then f is continuous at a.

Note: The converse is not always true. A function can be continuous


at a, but not differentiable at a. For instance, see the example above.

Hence, if f is differentiable on an interval, then it is continuous on the same


interval as well.
Basic Differentiation Formulas

Suppose f and g are differentiable functions, c is any real number, then

d
1. (c ) 0
dx

d d d
2. [ f ( x) g ( x )] f ( x) g ( x)
dx dx dx

d d d
3. [ f ( x ) g ( x )] f ( x) g ( x)
dx dx dx

d d
4. [c f ( x )] c f ( x)
dx dx

d d d
5. [ f ( x ) g ( x)] f ( x ) [ g ( x )] g ( x ) [ f ( x )]
dx dx dx

d d
g ( x) [ f ( x)] f ( x) [ g ( x)]
6. d f ( x) dx dx

dx g ( x) [ g ( x)]2

Or, in short-hand notations:


1. (c) = 0
2. [ f(x) + g(x)] = f (x) + g(x)
3. [ f(x) g(x)] = f (x) g(x)
4. [c f (x)] = c f (x)
5. [ f (x)g(x)] = f (x)g(x) + g(x)f (x)

f ( x) g ( x ) f ( x ) f ( x ) g ( x )
6. g ( x)
[ g ( x )]2

The Power Rule: For any real number n,


d
( x n ) n x n 1
dx

d
For n = 1, this means that ( x ) 1 x11 x 0 1 .
dx
d d
And if n = 0, then (x0 ) (1) 0 x 01 0 , which is consistent
dx dx
with the constant rule of differentiation (rule #1 above).

ex. The instantaneous rate of change of a line

Suppose f (x) = mx + b , where m and b are constants, then

f (x) = (mx) + (b) = m(x) + (b) = m(1) + 0 = m

Therefore, any linear function has a constant derivative equals to the slope of
its graph, which is a line of slope m. It says that the instantaneous rate of
change of a linear function is constant, and that the tangent line to the graph
of a line is always the line itself (because the tangent line has the same slope
as the line, and they obviously contain one common point, therefore they
have the same equation and are therefore the same line).

ex. Differentiate y = 2t3 t + t 2 + 9

y = 2(t3) (t ) + (t 2) + (9) = 2(3t2) t 1 + ( 2t 3) + 0

= 6t2 t 1 2t 3

2
ex. Differentiate s (t ) 5 t 43 t
t

This would be easier to do if we first rewrite s(t) in terms of powers of x.

s (t ) 5t 1 / 2 2t 1 / 2 4t 1 / 3 , then
1 ( 12 1) 1
1) ( 1)
1 1 3 2
2 1t 2 4 1 t 3 5 t 2 t 2 4 t 3
(
s (t ) 5 t 2 3
2 2 3

x 2 3x 2
ex. Differentiate f ( x)
x 2 3x 2

( x 2 3 x 2)( x 2 3 x 2) ( x 2 3x 2)( x 2 3 x 2)
f ( x)
( x 2 3 x 2) 2

( x 2 3 x 2)(2 x 3) ( x 2 3x 2)(2 x 3)

( x 2 3 x 2) 2

2 x 3 3x 2 x 5
ex. Differentiate g ( x)
x2

The easiest way to do this is to rewrite g(x) as

1 5
g ( x) 2 x 3 , then
x x2

g ( x ) 2( x ) (3) ( x 1 ) 5( x 2 ) 2 0 ( x 2 ) 5( 2 x 3 )

1 10
2 x 2 10 x 3 2
x2 x3
ex. Differentiate y x ( x 2 5 x 2)

Simplify first: y = x5/2 5x3/2 + 2x1/2.

5 3/ 2 3 1 5 15 1 / 2
y x 5 x 1 / 2 2 x 1 / 2 x 3 / 2 x x 1 / 2
2 2 2 2 2

The longer way to do this is by using the product rule:

1
y x ( x 2 5 x 2) ( x 2 5 x 2)( x ) x (2 x 5) ( x 2 5 x 2)( x 1 / 2 )
2
1 1 5
x 1 / 2 (2 x 5) ( x 2 5 x 2)( x 1 / 2 ) 2 x 3 / 2 5 x1 / 2 x 3 / 2 x 1 / 2 x 1 / 2
2 2 2

5 3 / 2 15 1 / 2
x x x 1 / 2
2 2

ex. Suppose the curves y1 = x2 + ax + b and y2 = cx x2 have a common


tangent line at the point (1, 0). Find the constants a, b, and c.

Both curves have a common point at (1, 0). Therefore, when x = 1,


both y-values are 0. Hence, 0 = 1 + a + b and 0 = c 1.
Hence c = 1 and a + b = 1.

Sharing a tangent line at (1, 0) means that both curves have the same
instantaneous rate of change when x = 1, i.e., y1(1) = y2(1).

y1 = 2x + a y1(1) = a + 2
y2 = c 2x y2(1) = c 2

Substitute in c = 1 and equate y1(1) = y2(1):


y1(1) = a + 2 = y2(1) = c 2 = 1
Hence a = 3, and b = 1 a = 2.

Therefore, a = 3, b = 2, and c = 1.